2009
DOI: 10.1007/s00198-009-0936-8
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter survey on profile of care for hip fracture: predictors of mortality and disability

Abstract: Delay in surgery is a major cause of mortality and disability at 6 months, and interventions to modify this pattern of care are urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(57 citation statements)
references
References 40 publications
0
52
2
3
Order By: Relevance
“…A similar prospective cohort study in Italy with 3,707 patients > 50 years of age found a similar risk (HR = 1.08; 95%CI: 1.06-1.09) 28 .…”
Section: Discussionmentioning
confidence: 63%
“…A similar prospective cohort study in Italy with 3,707 patients > 50 years of age found a similar risk (HR = 1.08; 95%CI: 1.06-1.09) 28 .…”
Section: Discussionmentioning
confidence: 63%
“…La demora debe ser la mínima siempre que permita llevar a cabo la intervención en condiciones adecuadas, aunque la literatura muestra resultados controvertidos al medir su asociación con la mortalidad. Mientras dos estudios canadienses y dos norteamericanos no aprecian una relación estadística-mente significativa [11][12][13][14] , otros trabajos seña-lan que la mayor demora en la cirugía produce un aumento de la mortalidad [15][16][17] . Aunque la mayor parte de los trabajos de la literatura consisten, como el nuestro, en estudios transversales basados en el CMBD, es difícil comparar los resultados, ya que las metodologías no son siempre las mismas sin que se pueda encontrar un patrón definido.…”
Section: Discussionunclassified
“…Acute pain resulting from a hip fracture and related surgery can restrict the mobility recovery leading to overall activity restriction. According to previous studies, other suggested predictors of poor recovery after a hip fracture are clinical condition, gender and type of surgical treatment , Maggi et al 2010, Holt et al 2008a, Holt et al 2008b). …”
Section: Mobility Recovery After Hip Fracturementioning
confidence: 99%
“…In addition, living alone, higher age, physical disability and mobility limitation before the fracture were risk factors for institutionalization (Agusti et al 2012, Vochteloo et al 2012. Risk factors for mortality after a hip fracture are higher age, male gender, comorbidity, cancer, functional inability and treatment with opiates, delayed surgery, major postoperative complications and use of assistive devices (Agusti et al 2012, Alegre-Lopez et al 2005, Maggi et al 2010, Paksima et al 2008. Bone medication (Agusti et al 2012, Nurmi-Luthje et al 2011 as well as calcium and vitamin D supplements (Nurmi-Luthje et al 2011) are associated with deceased mortality risk.…”
Section: Other Serious Consequences 222mentioning
confidence: 99%